The effect of environmental stressors perceived by surgical intensive care unit patients on hopelessness level - Güneş, Dilek; Okşak, Elif (My University, 2024)
The aim of the research was to determine the effects of environmental stressors perceived by patients hospitalized in the surgical intensive care unit on hopelessness level. This descriptive research was performed between September 2023 and February 2024. The population of the study included all adult patients hospitalized in the Surgical Intensive Care Clinic of a City Hospital in Eastern Türkiye. The sample of the study includes 230 patients selected by random sampling method from this population. We used Personal Information Form, Intensive Care Unit Environmental Stressors Scale (ICUESS) and Beck Hopelessness Scale (BHS) to collect the data. Descriptive statistics, t-test, ANOVA, and correlation analysis tests were used to evaluate the data. The ICUESS mean score of the patients participated in the study was found to be at a high level with 102.13±15.95. Beck hopelessness scale score mean was found to be at a mild level with 6.36±5.78. It was found that the patients' gender, age, educational status, chronic disease status and previous intensive care experience affected the level of hopelessness. The relationship between ICUESS and BHS scores of the patients included in the study was examined and it was found that there was a low level of positive significant relationship between them (r: 0.162, p: 0.014). The hopelessness level of patients in surgical intensive care units was found to increase as the level of exposure to environmental stressors increased. It may be recommended to identify environmental stressors affecting the hopelessness level of patients and to implement interventions to reduce them.
Keywords: Nurse; Intensive care; hopelessness; environmental stressor